Effect of Spray Angle and Flow Rate on Improving PV Panel Performance: Experimental and Theoretical Study (American Journal of Agricultural Science, Engineering, and Technology, 2022)
A spray cooling system is used to improve the efficiency of solar cells discussed in this article. Cooling of solar panels is a significant factor that affects their performance. This experiment explores the effects of spray angle, nozzle to PV cell distance, nozzle number, on panel performance. A test rig was created for this purpose. The spray angles ranged from (10 to 45 %). When the spray angle is reduced to 20°, the electrical efficiency of the PV panel climbs to 18.763 percent, while the average PV panel temperature drops from 60 to 26 degrees Celsius (for non-cooled PV). Additionally, the distance between the nozzle and the PV panel was increased from 10 to 55 centimeters. With a 24.45% increase in power production, the best result was reached for the shortest distance. The results of the water spray system show that the greatest efficiency was reached.